2015
DOI: 10.1371/journal.pone.0132984
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Control of Macrophage Shape Transition towards an Atypical Elongated Phenotype by Histone Deacetylase Activity

Abstract: Inflammatory chronic pathologies are complex processes characterized by an imbalance between the resolution of the inflammatory phase and the establishment of tissue repair. The main players in these inflammatory pathologies are bone marrow derived monocytes (BMDMs). However, how monocyte differentiation is modulated to give rise to specific macrophage subpopulations (M1 or M2) that may either maintain the chronic inflammatory process or lead to wound healing is still unclear. Considering that inhibitors of Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 27 publications
4
39
0
Order By: Relevance
“…Class I and II HDACs are crucial for the proliferation and differentiation of bone marrow-derived monocytes (BMDMs) into macrophages and DC cells. For instance, under the treatment of TSA (a class I and II HDAC inhibitor), the amplification of murine myeloid progenitors is blocked and, in turn, differentiate into an elongated morphology of mixed M1/M2 profile, instead of the normal pancake-like shape of M1 inflammatory macrophages [37]. In addition, TFs associated with HDAC complexes shows dynamic changes during premonocyte to monocyte differentiation.…”
Section: Granulocyte-monocyte Lineage Terminal Differentiationmentioning
confidence: 99%
“…Class I and II HDACs are crucial for the proliferation and differentiation of bone marrow-derived monocytes (BMDMs) into macrophages and DC cells. For instance, under the treatment of TSA (a class I and II HDAC inhibitor), the amplification of murine myeloid progenitors is blocked and, in turn, differentiate into an elongated morphology of mixed M1/M2 profile, instead of the normal pancake-like shape of M1 inflammatory macrophages [37]. In addition, TFs associated with HDAC complexes shows dynamic changes during premonocyte to monocyte differentiation.…”
Section: Granulocyte-monocyte Lineage Terminal Differentiationmentioning
confidence: 99%
“…Additionally, it also suppresses the expression of cytokines and chemokines of ROS. In addition, macrophages exhibit an overexpression of IL6 and the IL6 receptor (IL6R) when stimulated by LPS [95]. However, the presence of the HDACi ITF2357 has been shown to reduce the expression of IL6 and IL6R [96].…”
Section: Epigenetic Modifiers and Macrophage Polarizationmentioning
confidence: 99%
“…Pharmacological and genetic studies showed that both class I and II HDAC promote an M1 phenotype (recently reviewed in Kapellos and Iqbal, 2016). Consequently, HDAC blockade with the pan-HDAC inhibitor TSA has been reported to polarize macrophages toward an alternatively activated phenotype and to the development of mixed M1/M2 phenotypes (Cabanel et al, 2015). However, epigenetic control of M1 and M2 phenotypes is a complex phenomenon linked to the inherent transient nature of cell polarization, as different activation states can coexist or evolve during disease progression (Martinez and Gordon, 2014), or possibly to the different macrophage populations in the different organs.…”
Section: Ms-275 and Pancreatic Inflammationmentioning
confidence: 99%